ANALYSIS OF INCOME LONG-YAM BUSINESS IN NAGARI TALANG MAUR SUB-DISTRICT MUNGKA DISTRICT LIMA PULUH KOTA WEST SUMATRA POVINCE - Fantia, Sri Rahayu; Zulkarnaini, Zulkarnaini; Hendrik, Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Research on analysis of Long-yam business income in Nagari Talang Maur.Had done in April 2018 in Nagari Talang Maur Sub District Mungka District of Lima Puluh Kota in West Sumatera Province.The purpose of this research to find out the amount of income and profit investment and the feasibility of Long-yam business. The method used is a survey method with responden of 6 Long-yam entrepreneurs. The average of investment is IDR 688. 992. 247, the average of business income is IDR 4.188.600.000 and the average profit is IDR 607. 011. 238. Based on the investment, income, and profits earned the Long-yam business in Nagari Talang Maur is feasible continued, because meets the requirements and feasibility the average Revenue Cost Of Ratio (RCR) is more than 1 which means that the business is profitable with RCR is 1,31 and average Payback Period Of Capital (PPC) is 1,13 period. Which means business financial return of business Long-yam it take 24 months. Keywords: Analisys, Business Income, Long-yam, Talang Maur Village